Clinical relevance and utility of GAD65 antibodies in neurological disease: an eight year cohort study. Issue 9 (12th August 2022) - Brown, Rachel; Thomas-Black, Gilbert; Garcia-Moreno, Hector; Chapman, Miles; Chou, Michael; Hart, Melanie; Fleszar, Zofia; Zandi, Michael; Giunti, Paola; Lunn, Michael P
Abstract : Neurological syndromes associated with glutamic acid decarboxylase (GAD) antibodies provide a challenge in understanding disease pathogenesis, interpreting antibody results, and deciding manage- ment. We retrospectively reviewed 277 patients with positive anti-GAD antibodies (≥ 10 IU/mL) at our centre between 2012-2020. 154 (56%) had one or more neurological disorders including 27 stiff person spectrum disorders (SPSD) (18%), 20 cerebellar ataxia (13%), 18 epilepsy (12%), 18 encephalitis (12%), 12 'mixed' (8%), and 59 other neurological disorders (38%). Co-existing autoimmunity was common; 57 (33%) had diabetes and 46 autoimmune thyroid disease (30%). A wide range of GAD titres was seen, but serum GAD antibody titres were significantly higher in patients with 'classical' GAD antibody syndromes than other neurological disorders (p<0.0001) or diabetes only (p<0.0001). In patients with 'classical' GAD antibody syndromes, both specific neurological syndrome and the presence of diabetes influenced serum antibody titres; neurological syndrome also affected CSF titres. Patients with SPSD or encephalitis were most likely to receive immunotherapy and the most likely to respond to treatment. Overall, GAD antibody titres were not associated with response to treatment. This is largest GAD-antibody cohort reported and together these data provide key lessons for understanding and interpreting GAD antibody-associated syndromes in clinical practice.